The Power of Visual Learning: Audio-Visual Health Education to Combat Stunting in Toddlers - Saindah, Sopia Nur (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: The aim of this study was to determine the effect of health education using audio-visual media on mothers' knowledge about stunting in toddlers. Methodology: The research was quantitative, using a pre-experimental design with a one-group pretest-posttest design. The sample consisted of 34 mothers with toddlers in Sitardas Village. Main Findings: The results of the study showed that the average score of mothers' knowledge about stunting before health education using audio-visual media was 6.12 and after health education using audio-visual media, there was an increase in knowledge of 9.18. Based on analysis using the Wilcoxon test, a p-value of 0.000 was obtained, which means there is an effect of health education using audio-visual media on mothers' knowledge about stunting in toddlers. Novelty/Originality of this study: This research is novel in that it examines the effectiveness of audiovisual media in health education for mothers regarding stunting in toddlers. The use of interactive media provides a more engaging and understandable approach, potentially significantly increasing mothers' knowledge and becoming a more effective educational strategy at the community level.